On integral transforms and matrix functions - Eltayeb, Hassan; Kilicman, Adem; Agarwal, Ravi P. (Hindawi Publishing Corporation, 2011)
The Sumudu transform of certain elementary matrix functions is obtained. These transforms are then used to solve the differential equation of a general linear conservative vibration system, a vibrating system with a special type of viscous damping.